Calidad de lana producida por ovinos de las parroquias rurales del cantón Saquisilí - Venegas López, Jimmy Santiago (2023)
The present study was carried out in the rural parishes of the Saquisili canton, with the objective of evaluating the quality of wool from sheep of the Corriedale, Criollo and Merino breeds. Wool samples were taken from 60 sheep, which were analyzed in the laboratory using Fibrelux equipment. The analysis of the data obtained from the samples was carried out through the method of descriptive statistics, using quantitative and qualitative variables that allowed evaluating the quality of wool. Contrasting the data, the following results were obtained for the Corriedale breed, the average fineness: 27.16 ± 0.50 (μ) the lower limit: 22.73, upper limit: 29.93. Wick Length: 72.25 ± 2.89 mm, lower limit 40 mm and upper limit 90 mm, Crimpness or waviness: 5.55 ± 0.23, lower limit 4, upper limit: 8 and variable qualitative resistance: 4 in high, on average 13 samples and 3 with low resistance. For the Criolla breed, the average fineness: 24.95 ± 0.67 μ, lower limit 21.1 and upper limit 30.4. The length of the wick 53.90 ± 1.99 mm lower limit 45 and upper limit 72, the Crimpness or waviness 3.70 ± 0.25, lower limit 3 and upper limit 6. The qualitative variable resistance 3 animals with high resistance, 5 with medium resistance and 12 with low resistance. While the Merino breed, the average fineness 22.51 ± 0.19 μ, lower limit 20.73, upper limit 23.8. The length of the strand 58.75 ± 2.09 mm, limits: 40 mm and 75 mm, the Crimpness or waviness: 5.47 ± 0.34, lower limit 4, upper limit 9. The qualitative variable resistance: 2 animals with high resistance, 12 with medium resistance and 6 with low resistance. A qualitative and quantitative comparison was carried out between sheep of the breeds that were the subject of this study, observing significant differences in terms of p values. The statistical difference evidenced is referred to the climate and nutrition factors that are related to the climatic levels in which the herds are raised. These factors have a direct influence on the quality of the fiber itself, which is of great importance for the textile industry.